Research on brillouin random fiber laser with half-open cavity - Zhang, Shuyuan (2016)
This dissertation mainly studies the characteristics of multi-wavelength output RFL based on SBS and EDF gain. Two different structures of RFL are proposed and demonstrated in this article, their output properties have been analyzed as well. The first one is a ring structure RFL uses a half-open cavity. Output wavelength is flattened and has high OSNR value, besides, to improve the quantity of output channels, ones can control and modify the BP power and 980nm pump power. A four output channels with line-width of about 0.022nm and frequency spacing of about 0.088nm is obtained.Besides, the stability of this proposed RFL has been proved, which is important in optical communication applications. The second linear cavity RFL achieved a more intensive stable multi-wavelength lasing output by using a CFBG. Reviewed on the traditional multi-wavelength FL incorporating mirrors or optical circulators as resonant cavities, the previous researches of RFL basically have high peak power discrepancy between odd and even Stokes lines because of low reflection of open-cavity structure. By incorporating a chirped fiber Bragg grating, the reflection of Stokes lines can be improved effectively, thus there is no obvious discrepancy can be observed in the second proposed RFL in this dissertation, the flatness of output channels is achieved. A brief history and development of RFL has been reviewed in Chapter 2. Basic classification of RFL has been introduced, examples and applications of them are given. Two newly proposed structures and potential RFL are successfully demonstrated in this dissertation. Output spectrum properties and output power characteristics of both two random fiber lasers are analyzed, and the four wavelength mixing process is also presented in this article in order to explain the generation of RFL more clearly. Generation threshold and output power of common RFL are discussed in Chapter 4 to investigate the RDF mechanism theoretically. Experimental results are conducted to support the theoretical proposal as well. For future work, more efforts will be given to improve the OSNR value to satisfy the wide applications of optical network communication system such as WDM system and optical fiber sensor. A new method is proposed to increase the OSNR and density of output channels, a programmable filter can be used in the experiment setup. Every individual Stokes line can be extracted by the filter. Mode suppression can be observed after the output spectrum being filtered. Besides the spectrum line-width can also be reduced, which is decided by the transmission bandwidth of the filter. Further experiments of wavelength extraction and theoretical mechanism should be studied.